The think factory : - Conway, Susan (John Wiley & Sons, Inc., 2007)
The debut title in Wiley’s Microsoft Executive Circle Series, The Think Factory shows you—using case studies and sample improvement plans—how intangibles such as collaboration and business intelligence interact to create tangible value and identifies the best practices for expanding your company’s investment in people and procedures.